Późnośredniowieczna i nowożytna ceramika kamionkowa z posesji przy ul. ks. Posadzego 5 w Poznaniu – z badań przeprowadzonych w latach 2010–2011 - Kowalczyk, Andrzej (Folia Praehistorica Posnaniensia, 2016)
This paper examines stoneware recovered during 2010–2011 excavations at ul. Ks. Posadzego 5, Poznań. The assemblage consists of 128 potsherds. Recognised and analysed were fragments of economic containers, sherds of mineral water bottles, plates produced in central-west England, vessels from Trzebiel, Bolesławiec and Waldenburg as well as Lusatian stoneware.